Assessment of Application Domains in Learning Islamic Education Skills in The 21st Century (Arfannur: Journal of Islamic Education, 2024)
This study aims to analyze the concept of application domain assessment in Islamic education learning that is relevant to 21st century skill development. The literature study approach is used to explore the various assessment theories, models, and practices that have been applied in the context of Islamic education, as well as how they can be adapted to meet the demands of 21st century skills. This study finds that the integration between the principles of Islamic education and the needs of 21st century skills requires a contextual and adaptive assessment approach. This finding is expected to make a theoretical and practical contribution to the development of an assessment model that is more relevant to the needs of the times, as well as provide a new direction for the implementation of Islamic education that is able to produce graduates who are not only religiously savvy but also ready to face global challenges.